Answer:
(x+1)^2+(y+1)^2=13
Step-by-step explanation:
Equation of a circle: (x – h)^2 + (y – k)^2 = r^2
center: (-1, -1)
radius: sqrt(6^2+4^2)/2=sqrt(52)/2=2sqrt(13)/2=sqrt(13)
Substitute those values in to get
(x+1)^2+(y+1)^2=13
Find difference i.e 100-82=18
if 82 is 100%, what about 18?
(18*100)/82= 21.951 ans
Answer:
7
Step-by-step explanation:
Answer:
Yes, they are equivalent.
Step-by-step explanation:
9 / 3 = 3
24 / 3 = 8
3:8 is just the simplified version of 9:24. This is due to 9:24 being divided by three, becoming 3:8.